Stability, Disequilibrium Awareness, and the Perception of New Opportunities - Fisher, Franklin M. (Econometrica, 1981)
This paper presents a model of general equilibrium stability in which agents understand that they are not at equilibrium. Rather, agents expect prices to change and contemplate the possibility that they may not be able to complete their own transactions. They optimize their actions taking account of such price changes and transaction constraints. It is shown that a necessary condition for instability is the continuing perception of new, previously unforeseen opportunities (real or imagined). Without this, old opportunities will be arbitraged away and the system will converge to equilibrium. The equilibrium approached will depend on the history of the system and may not be Walrasian if transaction constraints are present.